Cronobacter sakazakii, Cronobacter malonaticus, and Cronobacter dublinensis Genotyping Based on CRISPR Locus Diversity - Zeng, Haiyan; Li, Chengsi; He, Wenjing; Zhang, Jumei; Chen, Moutong; Lei, Tao; Wu, Haoming; Ling, Na; Cai, Shuzhen; Wang, Juan; Ding, Yu; Wu, Qingping (Frontiers in Microbiology, 2019)
Cronobacter strains harboring CRISPR-Cas systems are important foodborne pathogens that cause serious neonatal infections. CRISPR typing is a new molecular subtyping method to track the sources of pathogenic bacterial outbreaks and shows a promise in typing Cronobacter, however, this molecular typing procedure using routine PCR method has not been established. Therefore, the purpose of this study was to establish such methodology, 257 isolates of Cronobacter sakazakii, C. malonaticus, and C. dublinensis were used to verify the feasibility of the method. Results showed that 161 C. sakazakii strains could be divided into 129 CRISPR types (CTs), among which CT15 (n = 7) was the most prevalent CT followed by CT6 (n = 4). Further, 65 C. malonaticus strains were divided into 42 CTs and CT23 (n = 8) was the most prevalent followed by CT2, CT3, and CT13 (n = 4). Finally, 31 C. dublinensis strains belonged to 31 CTs. There was also a relationship among CT, sequence type (ST), food types, and serotype. Compared to multi-locus sequence typing (MLST), this new molecular method has greater power to distinguish similar strains and had better accordance with whole genome sequence typing (WGST). More importantly, some lineages were found to harbor conserved ancestral spacers ahead of their divergent specific spacer sequences; this can be exploited to infer the divergent evolution of Cronobacter and provide phylogenetic information reflecting common origins. Compared to WGST, CRISPR typing method is simpler and more affordable, it could be used to identify sources of Cronobacter food-borne outbreaks, from clinical cases to food sources and the production sites.